1999
DOI: 10.1070/qe1999v029n12abeh001630
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the optical characteristics of turbid media by the laser optoacoustic method

Abstract: Hydrogenated diamond-like carbon (DLC) films were deposited on Si (100) wafers by a plasma enhanced chemical vapour deposition technique using CH 4 plus Ar as the feedstock. The friction and wear properties of the resulting films under different relative humidities, ranging from 5% to 100%, in a nitrogen environment, were measured using a ball-on-disc tribometer, with Si 3 N 4 balls as the counterparts. The friction surfaces of the films and Si 3 N 4 balls were observed on a scanning electron microscope, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Behind the maxima the curves decay exponentially with the degree of (-L2 PaPc(i _ g)), where Lm 5 the sample thickness. This is in agreement with [9]. It should be noted here that the lower point of the curves is above the zero level because about some hundred photons reach the forward detector.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Behind the maxima the curves decay exponentially with the degree of (-L2 PaPc(i _ g)), where Lm 5 the sample thickness. This is in agreement with [9]. It should be noted here that the lower point of the curves is above the zero level because about some hundred photons reach the forward detector.…”
Section: Resultssupporting
confidence: 87%
“…The total intensity consists of the scattered light and the incident light. The position of the maximum Zmax depends on the properties of the medium and it is situated at the depth of 1 12 [9]. It takes place not only for continuous radiation but also for quasi-stationary pulses, which duration exceeds the photon lifetime in the medium (ttac/nY', where c is speed of light in vacuum, n is refractive index ofthe medium, or the propagation time Lmn/c (if 1.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the measured values of μ a are limited from below. In our previous papers, we demonstrated that the minimum value of light absorption that can be readily measured with the OA technique using a tabletop setup and conventional mJ nanosecond lasers is of an order of μ a  ∼ 0.05 [47]. However, the smaller is light absorption, the larger should be the depth (μa1) of the sample cell.…”
Section: Discussionmentioning
confidence: 99%
“…To split out the absorption and reduced scattering coefficients from the effective attenuation coefficient, we can measure either the amplitude of photoacoustic generation in the medium [2] or the photon transport mean path [6]. However, the former method necessitates measuring several physical and system parameters (which are usually unknown), while the latter poses very high requirements for the transducer (ultra-wide bandwidth) and the detection channel (very fast sampling frequency).…”
Section: Methodsmentioning
confidence: 99%